2016
DOI: 10.1016/j.bmc.2016.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-based peptidomimetics targeting neuropilin-1: Synthesis, molecular docking study and in vitro biological activities

Abstract: Neuropilin-1 (NRP-1), a transmembrane glycoprotein acting as a co-receptor of VEGF-A, is expressed by cancer and angiogenic endothelial cells and is involved in the angiogenesis process. Taking advantage of functionalities and stereodiversities of sugar derivatives, the design and the synthesis of carbohydrate based peptidomimetics are here described. One of these compounds (56) demonstrated inhibition of VEGF-A165 binding to NRP-1 (IC50 = 39 µM) and specificity for NRP-1 over VEGF-R2. Biological evaluations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 88 publications
0
21
1
2
Order By: Relevance
“…However, Tuftsin is not an ideal agent for use in clinical practice because of several limiting points including size, stability (susceptible to degradation by peptidases), lack of effective methods for delivery, low oral bioavailability, rapid excretion and poor transport properties through biologic membranes [ 26 , 27 ]. Thus, we developed a novel peptidomimetic named MR438 which has been built by molecular modeling based on well-known A7R peptide [ 16 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Tuftsin is not an ideal agent for use in clinical practice because of several limiting points including size, stability (susceptible to degradation by peptidases), lack of effective methods for delivery, low oral bioavailability, rapid excretion and poor transport properties through biologic membranes [ 26 , 27 ]. Thus, we developed a novel peptidomimetic named MR438 which has been built by molecular modeling based on well-known A7R peptide [ 16 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work focused on the development of peptides for targeting NRP-1 and we have proposed to use peptidomimetics for their theoretical stability [ 14 , 15 ]. We have recently designed and assessed some new sugar-based peptidomimetics targeting NRP-1 and one of them named MR438 presented a relevant in vitro affinity for NRP-1 (IC 50 of 88 μM) [ 16 ]. Tuftsin (TKPR: Thr-Lys-Pro-Arg) is a natural ligand of NRP-1 with a IC 50 of 25 μM [ 17 , 18 ] and it was used in our work as reference compound.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that other ligands containing a C-terminal arginine will also bind in a similar fashion [15]. Although protein-protein interactions have been considered challenging targets in drug discovery [16], a number of small molecules and peptides have been identified as inhibitors of the VEGF-A 165 -NRP1 interaction [17][18][19][20][21][22][23][24][25][26][27][28][29]. In some cases, it has been demonstrated that the inhibitors act through direct binding to the b1 domain of NRP1.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4E). Thus, all of compounds are able to partially mimic the terminal carboxyl contacts that are considered to be critical for anchoring the terminal Arg of CendR peptides 12,31,[38][39][40][41][42][44][45][46][47][48][49][50][51][52][53] (Figure 1C) or known small molecule mimetics and inhibitors that contain a terminal guanidyl from Arg moiety and carboxylic group 54,61,62 . Figure 4F).…”
Section: Series Analysis and Docked Binding Modesmentioning
confidence: 99%
“…Due to its role in cancer, NRP-1 has been a target for drug design for over 20 years. During this time, discovery efforts have focused on development of NRP-1 antibody therapies 9,[28][29][30][31][32][33] , including a recent dual-specificity antibody to VEGFA and NRP-1 32,33 , peptides that target transmembrane domain interactions 11,[34][35][36][37] or the CendR interaction site 12,31,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] , as well as small-molecules that target the CendR site [54][55][56][57][58][59][60][61] . With one exception 43 , the CendR site targeting peptides contain a CendR motif, even those which are cyclical 39,45,46,49 or branched 51,53 .…”
Section: Introductionmentioning
confidence: 99%